Studies on the behaviour of the Eurasian Lynx (Lynx lynx) in the “Alpenzoo” (Innsbruck) with focus on the activity pattern under various conditions - Müller, Katharina (2022)
Existing studies on the behaviour and activity pattern of the Eurasian lynx (Lynx lynx) rarely focus on animals living in captivity. Therefore, this thesis aimed to investigate the behaviour and activity pattern of lynxes living in a zoo under various conditions. Four camera traps were used to monitor the animals within their enclosure in the “Alpenzoo” (Innsbruck) for 87 days. A total of 488002 photos were collected and used for analysing the general activity pattern, the frequency of social and non-social behavioural acts, the avoidance of a certain area during visiting time, the usage of pathways, as well as the influence of the temperature on the activity. The general activity pattern of two different days was investigated by parting each 24 hours into sections of 2 hours for a better comparison for two of the camera traps, while for the other two the whole day was analysed at once and the results revealed a quite similar pattern of activity on the two days. The analysis of the behavioural acts showed a higher frequency of non-social than social behaviour during day and night. Contrasting to animals living in the wild, the lynxes in this study exhibited more diurnal than nocturnal behavioural acts. Moreover, the results showed the avoidance of a certain area during visiting time, as there were significantly more appearances for two of the three animals in this part of the enclosure during non-visiting time. When analysing the movement patterns, there was a certain level of randomness in the locomotion of the animals, however, the usage of specific pathways when moving through the enclosure was clearly detectable and therefore could be proved. The analysis of the influence of the temperature on the activity of the animals led to no clear results, as no significant decrease or increase in activity during various periods could be detected. Katharina Müller Masterarbeit Universität Innsbruck 2022